ASYLUM PROCEDURE IN LATVIA - A PART OF COMMON EUROPEAN ASYLUM SYSTEM - Adijāne, Iveta (Border Security and Management, 2018)
The Common European Asylum System (CEAS) conditions apply to Latvia. Development of the Common European Asylum System impacts Latvian legislation and has an effect on the work of judicial institutions. Any European Union scale change affects Latvia. Common European Asylum System conditions in Latvia are being met by direct implementation of the EU instructions. Well-considered position and evaluation of CEAS conditions according to Latvian interests is necessary. Goal of this article is to review demands of the Common European Asylum System towards the member states as well as concordance of the Latvian asylum procedure with conditions of the Common European Asylum System. Objectives of this research is to examine development of legislation in the EU and Latvia, to analyse and compare current legislation of the asylum procedure in the EU member states as well as to analyse impact of CEAS towards the asylum procedure in Latvia. In order to achieve objectives, following research methods were used: monographic research of theoretical and empirical sources in order to analyse and evaluate various asylum domain information, analytical method in order to acquire legislative content and verities, comparative method in order to discover differences in legislation of asylum procedure in the EU countries, systemic method in order to disclose interconnections in legislation, descriptive statistics method and correlation analysis in order to analyse process of the asylum procedure and determine interconnections in the asylum procedure time frame between legislation and practical instances in EU countries.